Disonansi kognitif pada perempuan pecandu pornografi - Rendy Alfiannoor Achmad; Ayunia Firdayati (Psychology Study Program, Faculty of Medicine, Universitas Lambung Mangkurat, 2019)
Based on a Google Trends survey, Indonesia is ranked as the world's top 10 consuming pornographic material for the types of keywords that are related to sex, and an average of 20% of all categories are conducted by student-aged adolescents. This study aims to describe how cognitive dissonance is experienced by women who are addicted to pornography. The method used in this study is a qualitative method with a case study approach. Data was collected by observation and interview, the subject of the study was a woman who had been exposed to pornography since sitting in elementary school. The results of the study explained that the source of the occurrence of cognitive dissonance of the subject was due to a discrepancy between the subject's beliefs and assessment of the new environment towards the subject's habit of watching pornographic videos. Cognitive dissonance experienced by women who are addicted to pornography is the emergence of feelings of anxiety, feelings of guilt, sin, feelings of fear are considered 'disgusting', and also feel their behavior is only a waste of time.